2017
DOI: 10.1007/s13348-017-0207-5
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic fractional perturbed control systems with fractional Brownian motion and Sobolev stochastic non local conditions

Abstract: This paper investigates the approximate controllability for Sobolev type stochastic perturbed control systems of fractional order with fractional Brownian motion and Sobolev fractional stochastic nonlocal conditions in a Hilbert space, A new set of sufficient conditions are established by using semigroup theory, fractional calculus, stochastic integrals for fractional Brownian motion, Banach's fixed point theorem. The results are obtained under the assumption that the associated linear system is approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Ahmed et al [28] investigated the approximate controllability of nonlocal Sobolev-type neutral fractional stochastic differential equations with fractional Brownian motion and Clarke subdifferential. Mourad et al [29] investigated stochastic fractional perturbed control systems with fractional Brownian motion and Sobolev stochastic nonlocal conditions. Mourad [30] established the approximate controllability of fractional neutral stochastic evolution equations in Hilbert spaces with fractional Brownian motion.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed et al [28] investigated the approximate controllability of nonlocal Sobolev-type neutral fractional stochastic differential equations with fractional Brownian motion and Clarke subdifferential. Mourad et al [29] investigated stochastic fractional perturbed control systems with fractional Brownian motion and Sobolev stochastic nonlocal conditions. Mourad [30] established the approximate controllability of fractional neutral stochastic evolution equations in Hilbert spaces with fractional Brownian motion.…”
Section: Introductionmentioning
confidence: 99%
“…4,[7][8][9] On the other hand, due to the existence of ubiquitous noise factors in nature, stochastic integro-differential equations emerge in biology, 10 finance, 11,12 and more. [13][14][15] Nowadays, stochastic fractional models such as stochastic Volterra integral equations (SVIEs) and stochastic fractional integro-differential equations (SFIDEs) have been increasingly employed in diverse areas such as problems in science and engineering, 16,17 mathematical finance, 18 dynamical systems in physics, 19 biology, 20,21 and medical technology. 22 However, in many cases, due to the presence of random factors in models, the exact solutions to these problems are hard to obtain.…”
Section: Introductionmentioning
confidence: 99%
“…The literature indicates that the FLE has much richer dynamic behaviors than the classical harmonic oscillator and is more beneficial to the description of real environments. Some scholars have also made attempts and explorations in this respect, and studies have shown that fractional dynamical systems based on fractional-order differential equations tend to have more abundant dynamic phenomena than integerorder stochastic dynamical systems under similar conditions [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%